2023
DOI: 10.1186/s42506-023-00139-3
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of seat belt use among drivers and passengers: a systematic review and meta-analysis

Abstract: Background Seat belts might save people’s lives in car accidents by preventing severe collision damage and keeping passengers safe from critical injuries. This meta-analysis was performed to assess the prevalence of seat belt use among drivers and passengers. Methods The databases of PubMed, Web of Science (WOS), and Google Scholar were searched from the beginning of 2000 to late December 2020 to identify studies that investigated the prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 87 publications
(22 reference statements)
0
0
0
Order By: Relevance
“…Research has shown that the prevalence of seat belt use is highest in drivers, followed by front seat passengers, and lastly rear seat passengers. Furthermore, women drivers, on average, used seatbelts more often than men drivers [ 13 ]. Understanding factors that influence seat belt compliance, such as passenger demographics and behavioral aspects, could also inform targeted interventions to enhance overall safety.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that the prevalence of seat belt use is highest in drivers, followed by front seat passengers, and lastly rear seat passengers. Furthermore, women drivers, on average, used seatbelts more often than men drivers [ 13 ]. Understanding factors that influence seat belt compliance, such as passenger demographics and behavioral aspects, could also inform targeted interventions to enhance overall safety.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies to investigate the effects of different factors on seatbelt wearing behavior. The use of seatbelts has been reported to be more among drivers than passengers [4]. Other variables, which have been tested for their significant effect on seatbelt wearing behavior include age, gender, awareness campaigns and previous accident experience.…”
Section: Introductionmentioning
confidence: 99%